Pelatihan Penyusunan Alat Peraktikum Sederhana bagi Asisten Laboratorium Fisika - Azmi, Irham; Pangga, Dwi; Ahzan, Sukainil; Mirawati, Baiq (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
The "Simple Teaching Aids Design Training" aimed to enhance the competencies of physics laboratory assistants in supporting experiment-based learning, particularly under limited laboratory facility conditions. The training employed In-Service Training (IST) and On-Service Training (OST) methods, involving 10 laboratory assistants from the Physics Education Program at Universitas Pendidikan Mandalika. Evaluation results indicated significant improvements in four main aspects: knowledge, skills, attitudes, and participant satisfaction. The average scores for material mastery reached 3.9 (adequate understanding), skills 3.7 (fairly skilled), attitudes and motivation 4.0 (motivated), and training satisfaction 3.7 (fairly satisfied). This training successfully enabled participants to comprehend basic electronics concepts, design, and utilize simple teaching aids relevant to physics learning. Furthermore, participants’ high motivation reflected the training’s success in encouraging their innovation and creativity. Despite the positive outcomes, there remains room for improvement, including the integration of digital technology in teaching aid design, the provision of more adequate training facilities, and sustainable mentoring programs. This program provides significant contributions to promoting more effective, efficient, and sustainable experiment-based learning while empowering laboratory assistants as learning innovators in higher education environments.